DESIGN OF A MANGO PICKING TOOL WITH USING QUALITY FUNCTION METHOD DEPLOYMENT (QFD) AND ERGONOMIC FOR DETERMINING STANDARD DIAMETER GRAND GALAH - Fauzi Ghani, Irvan; Susandi, Dony; Whydiantoro, Whydiantoro (Jurnal Mekanika dan Manufaktur, 2021)
Traditional mango pickers made from bamboo. The characteristics of the mango fruit picker tool can not be adjusted in short length so there are difficulties during use, such as reaching different tree heights. Long shapes make picking tools mango fruit difficult to carry. A fragile basket template. There is no standard handheld diameter galah so there are some users feel uncomfortable when grasping it because of smallness or greatness.he design of the mango fruit picker tool using Quality Function Deployment (QFD) can make the product based on the wishes and needs of the users of the mango pickers. Product Design With QFD This requires Customer Voices to compile House Of Quality primary needs for the users obtained from the Customer Voices this will be used as the basis for designing the picker tool mango fruit. Designing the product by applying the hand anthropometry data of the handheld diameter (Maximum) using the P50 percentile. The use of the 50thpercentile is intended that users with larger or smaller handheld diameters may grasp it.